2016
DOI: 10.1016/j.clinthera.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Current Challenges in Cancer Treatment

Abstract: Targeting single molecular abnormalities or cancer pathways has achieved good clinical responses that have modestly affected survival in some cancers. However, this approach to cancer treatment is still reductionist, and many challenges need to be met to improve treatment outcomes with our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
427
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 685 publications
(436 citation statements)
references
References 78 publications
1
427
0
8
Order By: Relevance
“…Molecular targeted therapy is an advanced treatment option in cancer therapy that has become a major focus in cancer research because of fewer side effects and higher efficacy than standard chemotherapy agents [38]. Several different molecules can be considered targets for therapy, such as members of the signal transduction pathway; however, clinical tests have determined that drug resistance can be achieved when the pathway is altered [3941].…”
Section: Mechanisms Of Cancer Cell Drug Resistancementioning
confidence: 99%
“…Molecular targeted therapy is an advanced treatment option in cancer therapy that has become a major focus in cancer research because of fewer side effects and higher efficacy than standard chemotherapy agents [38]. Several different molecules can be considered targets for therapy, such as members of the signal transduction pathway; however, clinical tests have determined that drug resistance can be achieved when the pathway is altered [3941].…”
Section: Mechanisms Of Cancer Cell Drug Resistancementioning
confidence: 99%
“…Current conventional chemotherapy has various limitations (i.e., severe adverse effects and resistance to treatment) (2); thus the identification of novel effective and selective antitumor compounds is mandatory. An excellent analysis of the current challenges and future objectives in the treatment of cancer reported that the continuously growing knowledge of molecular and cellular tumor biology has revolutionized cancer treatment towards: i) the technological improvement of tumor molecular profiling; and ii) the discovery of predictive molecular targets (3). …”
Section: Introductionmentioning
confidence: 99%
“…It is reported that 4,292,000 new cancer cases and 2,814,000 cancer deaths are predicted to occur in China in 2015 [1] and 1,688,780 new cancer cases and 600,920 cancer deaths will occur in United States in 2017 [2]. Despite current advances in surgery, chemotherapy, radiotherapy, targeted therapy and immunotherapy, cancer remains a leading cause of death and constitutes an enormous burden worldwide [3, 4]. One of the reasons affecting the tumor prognosis was lacking of effective early diagnostic method before progression and effective prognostic indicator for guiding the clinical treatment.…”
Section: Introductionmentioning
confidence: 99%